The Failed Invasion of Harmonia Axyridis in the Azores, Portugal: Climatic Restriction or Wrong Population Origin? - Vergara-Egert, P; Alaniz-Baeza, A (Blackwell Publishing Ltd, 2021)
We tested two questions: (i) whether the climatic conditions of the Azorean Islands in Portugal may have restricted the invasion of Harmonia axyridis across this archipelago and (ii) determine what population of this species could have a higher probability of invading the islands. We used MaxEnt to project the climate requirements of different H. axyridis populations from three regions of the world, and the potential global niche of the species in the Azorean islands. Then we assessed the suitability of the islands for each of the three H. axyridis populations and global potential niche through histograms analysis, Principal Component Analysis (PCA) of climate variables, and a variable-by-variable assessment of the suitability response curves compared with the climatic conditions of the Azores. Climatic conditions of the Azores are less suitable for the U.S. and native Asian populations of H. axyridis, and more suitable for European populations and the global potential niche. The PCA showed that the climatic conditions of the islands differed from the climatic requirements of H. axyridis. This difference is mainly explained by precipitation of the wettest month, isothermality, and the minimum temperature of the coldest month. We concluded that the climatic conditions of the Azores could have influenced the establishment and spread of H. axyridis on these islands from Europe. Our results showed that abiotic resistance represented by the climate of the potentially colonizable zones could hinder the establishment of invasive insects, but it could vary depending of the origin of the colonizing population. © 2020 Institute of Zoology, Chinese Academy of Sciences
Keywords: climatic suitability; Harlequin ladybird; Invasibility; invasive alien species; Niche analysis; Species Distribution Model